156 ANALYSIS OF A TARGETED RECEPTOR TYROSINE KINASE INHIBITOR IN THE TREATMENT OF ACUTE MYELOGENOUS LEUKEMIA. (1st January 2005) - Menzel, L. P.; Shankar, D. B.; Shah, N. P.; Hummerickhouse, R.; Hagey, A.; Sakamoto, K. M.; Moore, T. B.
Abstract : Receptor Tyrosine kinases (RTK) play an important role in cell signaling, proliferation, and differentiation. Increased activation or levels of RTKs have been reported in approximately 90% of acute myelogenous leukemias (AML). Therefore, a drug designed to specifically target and inhibit RTKs is a rational approach to treat AML. We studied the effects of the RTKI, ABT869, on proliferation of AML cells and normal bone marrow in vitro. Methods: Several myeloid leukemia cell lines were analyzed, including K562, NB-4, HL-60, KG-1, M-NFS-60, 32DCl.3, and TF-1. Cells were plated at a density of 2×10e5 cells/ml in growth media with ABT869 at concentrations between 100 μM to 1 pM. Cell viability was determined using Trypan Blue exclusion and MTT assays. Normal human bone marrow was plated in methylcellulose containing cytokines with or without ABT869. Results: ABT869 rapidly induced cell death in the AML cell lines tested at concentrations above 10μM. At drug concentrations of 1, 10 and 100 nM, greater than 70% inhibition of cell growth was observed compared to the DMSO control treated cells within 48 hours after treatment. We performed methylcellulose assays to test for sensitivity of normal human bone marrow cells to ABT869. After 14 days, little difference in colony number or morphology was observed up to 10 nM concentration of ABT869. We are testing the effects of ABT869 on primary AML cells in colony forming assays and in NOD/SCID mice to further establish the compound's efficacy in vitro and in vivo. Conclusions: Both growth factor-dependent cell lines (TF-1, 32D Cl.3, and NFS-60) and growth factor independent cell lines (KG-1, HL-60, and NB-4) were equally susceptible to the targeted receptor tyrosine kinase inhibitor, ABT869. In addition, physiologic concentrations of ABT869 did not affect the growth of normal human bone marrow progenitor cells in methylcellulose. Our results demonstrate that ABT869 may be a potentially effective drug in the treatment of patients with AML.